Spatially resolved measurements of H2O, HCl, CO, OCS, SO2, cloud opacity, and acid concentration in the Venus near‐infrared spectral windows. Issue 8 (13th August 2014) - Arney, Giada; Meadows, Victoria; Crisp, David; Schmidt, Sarah J.; Bailey, Jeremy; Robinson, Tyler
Abstract We observed Venus with the Apache Point Observatory 3.5 m telescope TripleSpec spectrograph (R = 3500, λ = 0.96–2.47 µm) on 1–3 March 2009 and on 25, 27, and 30 November and 2–4 December 2010. With these observations and synthetic spectra generated with the Spectral Mapping and Atmospheric Radiative Transfer model, we produce the first simultaneous maps of cloud opacity, acid concentration, water vapor (H2O), hydrogen chloride (HCl), carbon dioxide (CO), carbonyl sulfide (OCS), and sulfur dioxide (SO2) abundances in the Venusian lower atmosphere. Water measured at wavelengths near 1.18 µm (near‐surface) averages 29 ± 2ppm (2009) and 27 ± 2 ppm (2010) and measured near 1.74 µm (15–30 km) averages 33 ± 2 ppm (2009) and 32 ± 2 ppm (2010). Water in both these altitude ranges is spatially homogeneous. Water measured near 2.4 µm (30–45 km) averages 34 ± 2 ppm (2009) and 33 ± 3 ppm (2010) and is spatially inhomogeneous and variable. HCl is measured near 1.74 µm to be 0.41 ± 0.04 ppm (2009) and 0.42 ± 0.05 ppm (2010). CO and OCS (2.3–2.5 µm; 30–45 km in altitude) are spatially inhomogeneous and show anticorrelation. CO (35 km) averages 25 ± 3 ppm (2009) and 22 ± 2 ppm (2010). OCS (36 km) averages 0.44 ± 0.10 ppm (2009) and 0.57 ± 0.12 ppm (2010). SO2 measurements average 140 ± 37 ppm (2009) and 126 ± 32 ppm (2010). Many species display a hemispherical dichotomy in their distribution. We find considerable spatial variability suggesting active processes with conservation between species. The most variable regions are just below the Venus cloud deck, and these may be related to changes in atmospheric circulation or virga events.